Imaging-based observation of the pes region in the dromedary camel (Camelus dromedarius): computed tomography, 3D volume rendering, magnetic resonance imaging, and ultrasonography - Hamoda, Hazem; Elsaid, Fahmy Gad; Eldesoqui, Mamdouh; AL-Mosaibih, Mai A.; Fayad, Eman; Hussein, Mohamed K.; Hamed, Mohamed A.; Farrag, Foad; Abumandour, Mohamed; Shukry, Mustafa; Abdelmegeid, Mohamed; Yousef, Abanoub T.; et al. (Frontiers in Veterinary Science, 2025)
IntroductionOur investigations utilized computed tomography (CT), magnetic resonance imaging (MRI), and ultrasonography (US) to provide detailed anatomical information on the pes region of a one-humped camel, with a particular focus on 3D reconstruction volume-rendered CT (3DVR-CT).MethodsThis research utilized 16 pes regions from adult male Camelus dromedaries aged 8–10 years.ResultsA CT scan revealed a vertical bony septum that completely divides the internal medullary cavity of the fused large metatarsal bones along the fusion line, except for the distal one-fifth portion, where the septum was absent. MRI identified the ligaments of the fetlock joint, which include the axial and abaxial collateral ligaments, collateral sesamoidean ligaments, and palmar ligaments. US demonstrated that the deep digital flexor tendon (DDFT) had higher echogenicity than the superficial digital flexor tendon (SDFT) at all imaging levels, with the SDFT paratendon appearing hyperechoic, which differentiated it from both the SDFT and the suspensory ligament. Our application of CT and MRI imaging techniques revealed that the Manica flexoria and distal sesamoid bone were not observed. On MRI, the sole appeared as a layer of low signal intensity, while the digital cushion exhibited heterogeneous high signal intensity.Discussionthe evaluation of anatomical regions in Camelus dromedaries can now be performed using CT, MRI, and US with 3DVR-CT, greatly improving the diagnosis and treatment of various conditions and facilitating the interpretation of some clinical diseases in the pes region. These imaging modalities, particularly 3DVR-CT, serve as valuable tools for veterinary clinicians and researchers studying camel anatomy and pathology.